The moderating effect of algorithm literacy on Over-The-Top platform adoption - Liu, Lu; Mohd Faris De Costa, Mohd Feroz Shah De Costa; Muhammad, Muhamad Sufri; Gong, Shuhui; Liu, Bin (Elsevier B.V., 2024)
Nowadays people are living in an algorithm-saturated environment, particularly in media and internet contexts. The algorithm implies the collected user's data to predict, lead, and react to the user's behavior in cyberspace. The over-the-top (OTT) platforms are media providers that can directly deliver media content to end-users and offer personalized and customized content for users with algorithmic curation where the algorithms play a central role. Therefore, investigating the concept of algorithm literacy and its influence on users' behavior in OTT platforms and understanding its impact becomes crucial. Meanwhile, eight of those various theories and models of technology adoption were integrated to form the Unified Theory of Acceptance and Use of Technology (UTAUT), which offers a unified perspective for exploring behavioral intention to use new technology. Thus, this article conceptualizes how “algorithm literacy” affects the interaction between performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention to embrace OTT platforms.